EDUCATION MANAGEMENT IN DIGITAL SOCIETY - Izzati, Izzati; Baniati, Heti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The era of digitalization is a very real effort that will be faced by educational institutions are now marked by technological advances on the demand side of ongoing quality developments, so that the achievements of social and cultural changes in the school community is significant. So that from this problem education must be in managerial education that is able to respond to the direction of change. So that management education based on digitalization is an important effort that must be encouraged as the future strength of the institution and sufficient quality human resources. The development of science and technology covers all aspects, including aspects of education. Along with these conditions, various opportunities and challenges emerged, especially for the world of education. Therefore, to be able to seize opportunities as well as answer the challenges of society in the digital era, education must really be adapted to the conditions of society in general. The digital era cannot only be faced with technological development without involving social dynamics in it. In addition to preparing superior competitiveness, it is necessary to build public awareness and maturity in responding to current world developments, especially in the post truth era, when information flows profusely without clarity of truth. It is necessary to formulate a national strategic policy through awareness and maturity of thought as well as community education which needs to be adapted to meet the need for expertise in this era. From this research, there are several things that are suggested in facing the digital era, namely the need to change the application of the system in Islamic educational institutions towards digital transformation.